Knowledge, attitudes and application of evidence-based practice by third and fourth year undergraduate nursing students at the University of Rwanda (UR) - Iradukunda, Favorite (Division of Nursing and Midwifery, 2016)
Evidence-based practice (EBP) is an important component in improving the health care outcomes of a country's population. Despite the importance and relevance of EBP to nursing, nurses do not routinely understand and use evidence-based principles in their everyday practice. This may influence the attitudes and knowledge of students who do not become exposed to the practice of EBP during their training. Nurses, who are considered to be the backbone of the health care profession, especially in Sub-Saharan Africa, should be introduced to the basic principles of EBP during their pre-registration programmes. Moreover, EBP teaching input should be both theoretical and practical with continuity throughout the whole nursing programme. The aim of this study was to determine the knowledge of, attitudes towards and application of EBP by nursing students from the College of Medicine and Health Sciences at the University of Rwanda. The study design was quantitative, descriptive and non-experimental. A total of 82 students participated in the study. An anonymous, self-reported questionnaire was used to collect data from third- and fourth-year nursing students from the College of Medicine and Health Sciences. Ethical approval was obtained from the Human Research Ethics Committee at the University of Cape Town's Health Sciences Faculty, and from the Directorate of Science, Technology and Research at the Rwandan Ministry of Education.